Optimisasi Pemanfaatan Pupuk Vermikompos dalam Meningkatkan Pertumbuhan dan Hasil Tanaman Jagung di Tanah Entisol Pesisir Pantai - Riwandi Riwandi; Hasanudin Hasanudin; Anandyawati Anandyawati; Wuri Prameswari (Institut Pertanian Bogor, 2023)
Entisol has poor physical, chemical, and biological properties that limit the growth and yield of maize. This study aimed to obtain the correct dose of vermicompost to increase the growth and yield of maize on Entisols. The research was arranged using Randomized Block Design, consisted of 7 treatment doses of vermicompost fertilizer (0; 2.5; 5; 7.5; 10; 12.5; and 15 Mg ha-1 and 4 re;plications. The results showed that the dose of vermicompost significantly affected the growth and yield of maize in coastal entisol soils. The dose of 10 Mg ha-1 was the best on plant height, leaf number, fresh weight, plant dry weight, shoot fresh weight, fresh root weight, and shoot and root dry weight. Meanwhile, the dose of 12.5 Mg ha-1 produced the best maize yields for the fresh weight of husked ear per plant, fresh weight of unhusked ear per plant, and dry grain weight per plant, namely, 322.75 g, 286.66 g, and 173.4 g, respectively. The best results of fresh weight of husked ear per plot, fresh weight of unhusked ear per plot, and dry grain weight per plot were achieved by vermicomposting of 15 Mg ha-1, which were 11.28 kg, 9.72 kg, and 5.94 kg, respectively. Keywords: coastal, Entisol, maize, vermicompost, yield